2019
DOI: 10.1177/0960327119860173
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate ameliorates neural, mechanical, chemical, and electrical alterations in the murine model of heart failure

Abstract: Heart failure (HF) is a leading cause of hospitalization across the world and is known to cause ill-health and heavy economic losses. In the present study, a rat model of isoproterenol (ISO, 85 mg/kg subcutaneously for two subsequent days) induced HF was developed. ISO induces HF by its direct effect, that is, rise in left ventricular end-diastolic pressure (mechanical) and indirectly by altering the baroreflex (neural), electrocardiography (electrical), and development of oxidative stress and hyperli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“… 148 found that fenofibrate prevents the transformation of cardiac metabolic substrates in HF model dogs and moderately improves cardiac function. A study showed that fenofibrate promotes fatty acid oxidation in the mitochondria of isoproterenol-induced HF rats, increases myocardial energy metabolism and oxidative stress, and protects heart function 149 . In addition, fenofibrate also reducing aldosterone-induced myocardial hypertrophy, but it may not be related to fatty acid oxidation 150 .…”
Section: Potential Drugs For Reducing Hf By Regulating Energy Metabolismmentioning
confidence: 99%
“… 148 found that fenofibrate prevents the transformation of cardiac metabolic substrates in HF model dogs and moderately improves cardiac function. A study showed that fenofibrate promotes fatty acid oxidation in the mitochondria of isoproterenol-induced HF rats, increases myocardial energy metabolism and oxidative stress, and protects heart function 149 . In addition, fenofibrate also reducing aldosterone-induced myocardial hypertrophy, but it may not be related to fatty acid oxidation 150 .…”
Section: Potential Drugs For Reducing Hf By Regulating Energy Metabolismmentioning
confidence: 99%
“…Furthermore, PPARα-deficient mice are more prone to cardiac hypertrophy in response to pressure overload ( Smeets et al, 2008 ; Wu et al, 2019 ; Wang et al, 2021 ). In addition, PPARα agonist elevates its function to alleviate cardiac hypertrophy ( Kar and Bandyopadhyay, 2018 ; Zeng et al, 2018 ; Dhyani et al, 2019 ). In the present study, salidroside reduced the mRNA expressions of hypertrophic marker ANF and BNP, which indicates that cardiomyocyte hypertrophy induced by Ang II treatment is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…PPARα is a member of the nuclear receptor family of ligand-activated transcription factors and regulates the uptake, transport and oxidation of fatty acids ( Montaigne et al, 2021 ). The decline of protein expression and transcriptional activity of cardiac PPARα is widely observed in cardiac hypertrophy, and cardiac hypertrophy is enhanced in response to chronic pressure overload in mice of PPARα knockout ( Smeets et al, 2008 ; Wu et al, 2019 ; Wang et al, 2021 ); moreover, PPARα agonists can attenuate cardiac hypertrophy ( Kar and Bandyopadhyay, 2018 ; Zeng et al, 2018 ; Dhyani et al, 2019 ). Therefore, the regulation of PPARα function has become one of the important strategies against cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…An altered utilization of metabolic substrates is recognized as one of the biochemical hallmarks of the cardiac hypertrophy and failing heart ( Kumar et al, 2019 ). A number of studies indicated that cardiac energy metabolism occurred unavoidably in cardiac hypertrophy rat models induced by ISO or AAC ( Gao et al, 2015 ; Dhyani et al, 2019 ). CPT-1 mediates the uptake of long-chain fatty acids into mitochondria and plays an important role in the control and regulation of mitochondrial β-oxidation ( Jernberg et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although cardiac hypertrophy is known to occur due to oxidative stress, inflammation, and autophagy, the main cause has not been elucidated ( Li et al, 2016 ; Anthony et al, 2019 ; Geng et al, 2019 ). Recently, a number of studies report that metabolic dysfunction is a hallmark of cardiac hypertrophy and heart failure ( Tian et al, 2018 ; Dhyani et al, 2019 ). Previous findings in our laboratory and others have proved that the cardiac hypertrophy is also characterized by a metabolic switch in the utilization of energy source that uses glucose as an energy source rather than utilizing fatty acid ( Ingwall, 2009 ; Zou et al, 2013 ; Gao et al, 2015 ; Yue et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%